Immunophenotyping identifies distinct cellular signatures for systemic lupus erythematosus and lupus nephritis. Issue 1 (23rd November 2022) - Aw, Yi Tong V.; Whiley, Phillip J.; Lorenzo, Ayla May; Lea‐Henry, Tom; Shanmuganandam, Somasundhari; Stanley, Maurice; Babu, Sonia N.; Athanasopoulos, Vicki; Cappello, Jean; Ellyard, Julia I.; Cook, Matthew; Vinuesa, Carola; et al.
Abstract: Background: Systemic lupus erythematosus (SLE) is a complex systemic autoimmune disease characterized by development of autoantibodies and multiorgan involvement. Kidney involvement, termed lupus nephritis, has major impact on life expectancy. It is increasingly recognized that SLE is likely a common clinical manifestation of pathophysiologically diverse processes, and lupus nephritis has similarly been associated with several distinct immunological processes. We compared the immune cell phenotypes of individuals with SLE in the presence or absence of nephritis. Methods: Cryopreserved peripheral blood mononuclear cells from SLE patients with and without kidney involvement underwent flow cytometric analysis to identify major populations in T cells, B cells and myeloid lineages. Results: We compared the frequencies of lymphocyte populations in 69 SLE patients without nephritis, 20 SLE patients with nephritis, and 92 healthy blood donors. Patients with SLE and lupus nephritis (LN) had reduced marginal zone B cells ( P < 0.0001 in SLE; P = 0.001 in LN), memory B cells ( P = 0.002 in SLE; P = 0.001 in LN) and circulating T follicular helper (Tfh) memory cells ( P < 0.0001 in SLE and LN) compared to healthy donors. Patients with lupus nephritis had increase Th2 ( P < 0.0001) and T regulatory cells ( P < 0.0001) compared to both SLE patients without nephritis and healthy donors. Conclusion: SLE patients with and without lupus nephritis have distinct immunologic differences that may reflect the unique pathophysiological processes contributing to disease manifestations. Abstract : Flow cytometric analysis of circulating lymphocytes was used to examine the differences in cell populations between SLE patients with or without nephritis and healthy blood donors. Key points: Patients with SLE had reduced marginal zone B cells, memory B cells and circulating T follicular helper cells compared to healthy blood donors. Patients with lupus nephritis had increased Th2 and T regulatory cells compared to SLE patients without lupus nephritis and healthy blood donors.